Effect of Refeeding on Lipid Metabolism in Kamphaengsaen Beef Heifers - Phongchai Klinhom; Kanchana Markvichitr; Pravee Vijchulata; Sornthep Tumwasorn; Chaiyapoom Bunchasak; Apassara Choothesa (Agriculture and Natural Resources, 2006)
Five Kamphaengsaen (Charolais Crossbred) beef heifers were used to study lipid utilization during a 30-day controlled-feed realimentation period. Dry matter intake was adjusted according to individual metabolic body weight to provide the same energy intake as in the full feeding period. At the end of refeeding period the heifers showed better feed conversion ratio. Back fat thickness increased and returned to the same level as before restriction (0.284 vs. 0.262 cm.). The loin eye area exhibited slight accretion (less than 1% of the loin eye area at the onset of realimentation). Adipose tissue lipolytic rate remained elevated and the heifers also exhibited high rate of lipoprotein export as in the previous restriction period. Plasma albumin concentration was higher than the base-line concentration. NEFA concentration declined and tended to be less than the base line concentration level (86vs.127μ mol/l). Because the high lipolytic rate occurred at this period, less circulating NEFA concentration was suggested for the high NEFA uptake by the peripheral tissue. BHBA and glucose concentrations were rebounded toward the base-line concentrations. PUN concentration markedly declined with the level lower P<0.05 than the base-line concentration (9.2 vs.10.8 mg/dl).This might result from the decreasing rate of catabolism of labile protein reserved. In conclusion, it was found that during repletion, the heifers utilized fat as the essential source of fuel and decreased proteolysis in the body.